2019
DOI: 10.1007/s12350-018-1230-y
|View full text |Cite
|
Sign up to set email alerts
|

Improved diagnostic accuracy of thallium-201 myocardial perfusion single-photon emission computed tomography with CT attenuation correction

Abstract: CTAC significantly improved diagnostic performance primarily by increasing the specificity, and the improvements were significantly greater in obese patients and male patients. These findings suggest that CTAC should be applied to Tl-201 MPI as routine clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…In this issue of the journal, Huang et al, have contributed to this trend by showing the value of CT attenuation for thallium SPECT MPI imaging. 1 Although attenuation correction has been in clinical use since the early 1990s and attenuation correction with CT has been available since at least 2005, their publication contributes to the body of knowledge in several important ways. 2 Very few previous studies have evaluated attenuation correction for thallium imaging.…”
Section: See Related Article Pp Pp 1584-1595mentioning
confidence: 99%
“…In this issue of the journal, Huang et al, have contributed to this trend by showing the value of CT attenuation for thallium SPECT MPI imaging. 1 Although attenuation correction has been in clinical use since the early 1990s and attenuation correction with CT has been available since at least 2005, their publication contributes to the body of knowledge in several important ways. 2 Very few previous studies have evaluated attenuation correction for thallium imaging.…”
Section: See Related Article Pp Pp 1584-1595mentioning
confidence: 99%
“…Coronary artery diseases cause one third of all mortality per year worldwide; though, in the developing countries, proportion of referrals for myocardial perfusion imaging (MPI) have not been studied [1]. Therefore, single-photon emission computed tomography (SPECT) as a technique for myocardial perfusion imaging has been performed in many countries [2,3]. Moreover, myocardial perfusion scintigraphy (MPS) investigates patients with probable coronary artery disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have evaluated the effect of AC in the patient-based diagnostic performance for CAD and assessed its effect in individual coronary arteries with stenosis. For example, some studies have reported that AC can increase the specificity of detecting RCA stenosis (13)(14)(15), however the results have been inconsistent with regards to LAD and LCX disease. One study reported no difference in specificity (13), another showed decreased specificity (15), and another showed increased specificity (14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some studies have reported that AC can increase the specificity of detecting RCA stenosis (13)(14)(15), however the results have been inconsistent with regards to LAD and LCX disease. One study reported no difference in specificity (13), another showed decreased specificity (15), and another showed increased specificity (14). Furthermore, another study showed increased diagnostic sensitivity in three vessel territories, increased specificity in the LAD and LCX, but no change in the RCA (16).…”
Section: Introductionmentioning
confidence: 99%